2016
DOI: 10.1523/jneurosci.4498-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cortical Spreading Depression Induces NMDA Receptor Dependent Potassium Currents in Microglia

Abstract: Cortical spreading depression (CSD) is a propagating event of neuronal depolarization, which is considered as the cellular correlate of the migraine aura. It is characterized by a change in the intrinsic optical signal and by a negative DC potential shift. Microglia are the resident macrophages of the CNS and act as sensors for pathological changes. In the present study, we analyzed whether microglial cells might sense CSD by recording membrane currents from microglia in acutely isolated cortical mouse brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…SD facilitates microglia-to-neuron interactions, while microglia depletion alters the electrical threshold of SD elicitation SD travels across the cerebral cortex restricted to the ipsilateral hemisphere, 37 and microglia are supposed to detect changes in neuronal activity induced by SD. 26,38 To test the possible effect of repeated SDs on microglia, we first performed 2D morphology analysis on representative microglial cells sampled randomly from the ipsi-and the corresponding contralateral insular cortex of mice (Figure1(a) and (b)). We found a small, but significant decrease in the area of microglial cell bodies (ipsilateral: 36.14 mm 2 (median, 32.2-42.2 interquartile range), n ¼ 66 cells; contralateral: 38.84 mm 2 (33.6-44.36), n ¼ 79 cells from three mice), and the number of microglial processes originating from the soma was reduced by 17% (n ¼ 79 cells from three mice).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SD facilitates microglia-to-neuron interactions, while microglia depletion alters the electrical threshold of SD elicitation SD travels across the cerebral cortex restricted to the ipsilateral hemisphere, 37 and microglia are supposed to detect changes in neuronal activity induced by SD. 26,38 To test the possible effect of repeated SDs on microglia, we first performed 2D morphology analysis on representative microglial cells sampled randomly from the ipsi-and the corresponding contralateral insular cortex of mice (Figure1(a) and (b)). We found a small, but significant decrease in the area of microglial cell bodies (ipsilateral: 36.14 mm 2 (median, 32.2-42.2 interquartile range), n ¼ 66 cells; contralateral: 38.84 mm 2 (33.6-44.36), n ¼ 79 cells from three mice), and the number of microglial processes originating from the soma was reduced by 17% (n ¼ 79 cells from three mice).…”
Section: Resultsmentioning
confidence: 99%
“…23 Microglia react to SD by increased IL-1b release, 24,25 and enhanced outward potassium conductivity. 26 They have also been shown to remain reactive for days after series of SDs triggered in rats 27 and to modulate SD initiation ex vivo. 28 However, the mechanisms through which microglia may tune the susceptibility of the nervous tissue to SD are yet to be explored in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…While NOX2 in microglia is activated in response to neurotoxic stimulation (54), NMDA receptor stimulation is required for NOX2 activation in neurons (39), and we found that blockade of NMDARs by APV recapitulated the effect of NOX2 inhibition. Importantly, we cannot rule out a possible contribution of microglia, as the expression of NMDARs has been reported for microglia (71), although the presence of functional microglial NMDARs in situ is a matter of debate (72,73) and our microglial depletion experiments did not achieve complete ablation. Further experiments will also be needed to evaluate a potential contribution of astrocytes, which express both NMDARs and NOX.…”
Section: Discussionmentioning
confidence: 78%
“…Despite substantial evidence supporting that NMDAR activation stimulates microglia to adopt a reactive phenotype (A. M. Kaindl et al, ; Tikka & Koistinaho, ), more controversial has been the extent to which measurable NMDAR‐mediated membrane currents can be recorded electrophysiologically from microglia. Indeed, appreciable NMDAR‐mediated currents in response to brief (secs) agonist applications have been reported by several groups (Eun et al, ; Kaindl et al, ; Liu, Kalous, Werry, & Bennett, ; Morkuniene et al, ) and yet not by others (Eyo et al, ; Noda, Nakanishi, Nabekura, & Akaike, ; Wendt, Wogram, Korvers, & Kettenmann, ). Some of the controversy could be related to differences in the microglial inflammatory status between studies, a potentially important factor not always considered in studies published to date.…”
Section: Discussionmentioning
confidence: 98%